Design of Geography Materials Have Substances of Indonesian Geopolitics as Systemic Program Strengthening National Character - Sugiharto Sugiharto; Darwin Parlaungan Lubis; M. Taufik Rahmadi; Sendi Permana; Mulhady Putra (Randwick International of Social Science Journal, 2022)
This study aims to develop the design of geography learning materials containing Indonesian geopolitics as a systemic program to strengthen national character in the Department of Geography Education, Faculty of Social Sciences, State University of Medan. The specific target to be achieved is the production of textbooks on geography learning materials containing Indonesian geopolitics. The research method used is the R&D method by following the Borg & Gall procedure. The research subjects involved: lecturers in Political Geography courses; students as subjects for a limited group trial; and five experts for the validation of teaching materials. The instruments used were expert validation questionnaires, learning outcomes tests and observation sheets, which were analyzed using: qualitative descriptive analysis to analyze information about various field conditions; quantitative descriptive analysis used to analyze the scores given by the expert; and statistical analysis assisted by STATCAL software. The results showed that the textbooks developed were valid and suitable for learning Political Geography, as well as contributing to the systemic program of strengthening national character in campus life by placing six pillars of character, namely: citizenship, justice, honor, responsibility, caring, and being able to trust.